2011
DOI: 10.1074/jbc.m110.170597
|View full text |Cite
|
Sign up to set email alerts
|

Kir2.6 Regulates the Surface Expression of Kir2.x Inward Rectifier Potassium Channels

Abstract: Precise trafficking, localization, and activity of inward rectifier potassium Kir2 channels are important for shaping the electrical response of skeletal muscle. However, how coordinated trafficking occurs to target sites remains unclear. Kir2 channels are tetrameric assemblies of Kir2.x subunits. By immunocytochemistry we show that endogenous Kir2.1 and Kir2.2 are localized at the plasma membrane and T-tubules in rodent skeletal muscle. Recently, a new subunit, Kir2.6, present in human skeletal muscle, was id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 58 publications
1
33
0
1
Order By: Relevance
“…The report by Ryan et al (12) and ours indicate an important role of Kir2.6 in the regulation of skeletal muscle membrane potentials. During the course of our present study, Dassau et al (14) reported that Kir2.6 co-assembles with Kir2.1 and Kir2.2. Based on immunofluorescent staining of recombinant Kir2.6 in transfected rodent tissues, the authors suggested that Kir2.6 is predominantly distributed to the endoplasmic reticulum and functions as a dominant negative regulator of cell surface abundance of Kir2.x channels by retention in the endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The report by Ryan et al (12) and ours indicate an important role of Kir2.6 in the regulation of skeletal muscle membrane potentials. During the course of our present study, Dassau et al (14) reported that Kir2.6 co-assembles with Kir2.1 and Kir2.2. Based on immunofluorescent staining of recombinant Kir2.6 in transfected rodent tissues, the authors suggested that Kir2.6 is predominantly distributed to the endoplasmic reticulum and functions as a dominant negative regulator of cell surface abundance of Kir2.x channels by retention in the endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 82%
“…Kir2.1 channel is also expressed in skeletal muscle and reportedly forms heteromultimers with Kir2.6 (14). We thus compared Kir2.1 and Kir2.6 channel properties and explored potential interactions between disease mutant Kir2.6 and wild type Kir2.1.…”
Section: Kir26 Forms Heteromultimers With Kir21 and Kir26 Mutants mentioning
confidence: 99%
“…S2E and S3F and Table S1). Whereas there are conflicting reports about the location of ClC-1 in muscle (37,40), it is established that Kir channels are expressed in the transverse tubular system (44,45). A definitive confirmation of a partial detubulation will require optical methods that include electron microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Además, Parálisis Periódica Hipocalémica Tirotóxica se ha demostrado en el músculo estriado y cardíaco que la actividad de la bomba calcio ATPasa presente en el retículo sarcoplásmico, esta disminuida, permitiendo un retardo en la eliminación del calcio presente en el citoplasma, contribuyendo a la parálisis (11). Los ataques de parálisis perió-dica hipocaliémica tirotóxica pueden ser desencadenados por periodos de ejercicio intenso, la ingestión de dieta rica en carbohidratos o alcohol, trauma, estrés, exposición al frío, infección y fármacos como: diuréticos perdedores de potasio, insulina, amiodarona, beta miméticos, adrenalina, corticoides, piridostigmina, cosintropina y pilocarpina (6,20). La parálisis periódica hipocaliémica tirotóxica afecta principalmente a varones entre la segunda y cuarta década de vida (8), puede estar precedida de pródromos con calambres, rigidez y mialgias en miembros inferiores (6).…”
Section: Discussionunclassified